A case of disseminated perforating necrobiosis lipoidica. Issue 5 (27th March 2020) - Gori, Niccolò; Di Stefani, Alessandro; De Luca, Erika Valentina; Peris, Ketty
Abstract: Perforating necrobiosis lipoidica (PNL) is a granulomatous inflammatory skin disease that usually occurs in patients with diabetic. We present a case of a female patient affected by a disseminated form of necrobiosis lipoidica. Abstract : Perforating necrobiosis lipoidica (PNL) is a granulomatous inflammatory skin disease that usually occurs in patients with diabetic. We present a case of a female patient affected by a disseminated form of necrobiosis lipoidica.